Implementation Of Green Hospitals To Improve Hospital Sustainability In Indonesia: A Narrative Literature Review - Nadira Kesya (International Journal of Health Engineering and Technology, 2026)
Hospitals generate waste and consume large amounts of energy, which negatively impact the environment. The Green Hospital concept was developed to support environmental sustainability in healthcare facilities. To examine the implementation strategies of Green Hospital and its impact on hospital sustainability in Indonesia. A narrative literature review was conducted by searching articles from Google Scholar and PubMed using keywords related to Green Hospital. A total of 10 articles (2015–2024) were thematically analyzed. Several hospitals have implemented Green Hospital principles such as energy efficiency, waste management, and green open space. RSUPN Dr. Cipto Mangunkusumo achieved the highest implementation score, while some hospitals still face challenges in human resources, infrastructure, and funding. The implementation of Green Hospital shows positive impacts on sustainability but still requires policy support and capacity building in hospitals.